Financial Strain and Psychological Distress: Do Strains in the Work-Family Interface Mediate the Effects?. (July 2021) - Chai, Lei; Schieman, Scott; Bierman, Alex
Analyzing three waves of the Canadian Work Stress and Health Study with cross-lagged models, we asked: (1) How do two distinct directions of strain in the work-family interface—work-to-family conflict and family-to-work conflict—mediate the relationship between financial strain and psychological distress? and (2) Is reverse causality a possibility in these dynamics? Our results indicate that work-to-family conflict at Wave 2 mediates the relationship between financial strain at Wave 1 and distress at Wave 3, but family-to-work conflict does not function as a mediator. Financial strain is therefore indirectly associated with subsequently higher levels of distress. In tests for reverse causality, we found little evidence that distress is associated with subsequently higher levels of financial strain—and neither work-to-family conflict nor family-to-work conflict at Wave 2 mediates that relationship. We interpret our findings within the conceptual and empirical ideas associated with stress proliferation, social causation, and social selection/drift.